2022
DOI: 10.1002/ajmg.c.32008
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant tubulointerstitial kidney disease: A review

Abstract: The clinical characteristics of autosomal dominant tubulointerstitial kidney disease (ADTKD) include bland urinary sediment, slowly progressive chronic kidney disease (CKD) with many patients reaching end stage renal disease (ESRD) between age 20 and 70 years, and autosomal dominant inheritance. Due to advances in genetic diagnosis, ADTKD is becoming increasingly recognized as a cause of CKD. Pathogenic variants in UMOD, MUC1, and REN are the most common causes of ADTKD. ADTKD‐UMOD is also associated with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
(167 reference statements)
0
1
0
Order By: Relevance
“… 37 We showed that the ALG5 mutation affected uromodulin trafficking, with abnormal deposition of uromodulin within the ER. Abnormal deposition of uromodulin has been identified as a consistent pathologic finding in ADTKD- UMOD , 38 where the clinical phenotype of tubulointerstitial fibrosis and CKD is similar to ADPKD- ALG5 . Thus, we hypothesize a 2-fold pathophysiologic process, where aberrant glycosylation of PC1 and polycystin-2 leads to decreased PC1 and polycystin-2 surface expression, further leading to cystic disease.…”
Section: Discussionmentioning
confidence: 93%
“… 37 We showed that the ALG5 mutation affected uromodulin trafficking, with abnormal deposition of uromodulin within the ER. Abnormal deposition of uromodulin has been identified as a consistent pathologic finding in ADTKD- UMOD , 38 where the clinical phenotype of tubulointerstitial fibrosis and CKD is similar to ADPKD- ALG5 . Thus, we hypothesize a 2-fold pathophysiologic process, where aberrant glycosylation of PC1 and polycystin-2 leads to decreased PC1 and polycystin-2 surface expression, further leading to cystic disease.…”
Section: Discussionmentioning
confidence: 93%
“…Unfortunately, genotyping for the vast majority of MUC1 mutations is currently not performed in any commercial genetics laboratory, as these mutations are not identified by standard Sanger sequencing. 38 Mucin-1 plays an important role in other respiratory tract infections 14 , and we need to extend our studies in patients with ADTKD- MUC1 to other pulmonary infections.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing can provide information on clinical management, prognosis, disease mitigation, transplant decision-making and reproductive planning. 1 , 6 , 7 , 8 , 9 However, there are associated complexities which arise from testing such as diagnostic versus predictive testing (testing at-risk individuals) and variant interpretation. This can lead to a lack of confidence about incorporating genomics into clinical practice.…”
Section: Introductionmentioning
confidence: 99%